3,3′-Diindolylmethane Induces G1 Arrest and Apoptosis in Human Acute T-Cell Lymphoblastic Leukemia Cells - Shorey, Lyndsey E.; Hagman, Amanda M.; Williams, David E.; Ho, Emily; Dashwood, Roderick H.; Benninghoff, Abby D. (PLOS ONE, 2012)
Certain bioactive food components, including indole-3-carbinol (I3C) and 3,3′-diindolylmethane (DIM) from cruciferous vegetables, have been shown to target cellular pathways regulating carcinogenesis. Previously, our laboratory showed that dietary I3C is an effective transplacental chemopreventive agent in a dibenzo[def,p]chrysene (DBC)-dependent model of murine T-cell lymphoblastic lymphoma. The primary objective of the present study was to extend our chemoprevention studies in mice to an analogous human neoplasm in cell culture. Therefore, we tested the hypothesis that I3C or DIM may be chemotherapeutic in human T-cell acute lymphoblastic leukemia (T-ALL) cells. Treatment of the T-ALL cell lines CCRF-CEM, CCRF-HSB2, SUP-T1 and Jurkat with DIM in vitro significantly reduced cell proliferation and viability at concentrations 8- to 25-fold lower than the parent compound I3C. DIM (7.5 µM) arrested CEM and HSB2 cells at the G1 phase of the cell cycle and 15 µM DIM significantly increased the percentage of apoptotic cells in all T-ALL lines. In CEM cells, DIM reduced protein expression of cyclin dependent kinases 4 and 6 (CDK4, CDK6) and D-type cyclin 3 (CCND3); DIM also significantly altered expression of eight transcripts related to human apoptosis (BCL2L10, CD40LG, HRK, TNF, TNFRSF1A, TNFRSF25, TNFSF8, TRAF4). Similar anticancer effects of DIM were observed in vivo. Dietary exposure to 100 ppm DIM significantly decreased the rate of growth of human CEM xenografts in immunodeficient SCID mice, reduced final tumor size by 44% and increased the apoptotic index compared to control-fed mice. Taken together, our results demonstrate a potential for therapeutic application of DIM in T-ALL.